Buffalo calf rearing practices followed at peri-urban buffalo farms of Surat city, Gujarat - G. P. SABAPARA, G. P. SABAPARA (Indian Journal of Animal Production and Management, 2019)
A field survey was conducted to collect the information on buffalo calf rearing management practicesfollowed by buffalo owners in Peri-urban areas of Surat city of Gujarat. The results revealed that 98%of the respondents attended calving and cleaned the calves soon after parturition. Ninety six percent ofrespondents did not practice ligation, cutting and disinfection of the naval cord of the calf and 42% ofrespondents fed colostrum to new born calf within one hour of birth. None of respondents followed weaningpractices and 42% of respondents allowed calves to suckle their dams till lactation ceased. Sixty percentof respondents provided green fodders at the age of two months and none of respondents provided calfstarter to the calves. None of respondents practiced castration of male calves and 34% of respondentsgave anthelmetics to the calves regularly. Only 14% of respondents provided jacketing as well as beddingin order to protect their calves from cold during winter season.